Serotonergic Antidepressants and Risk for Traumatic Intracranial Bleeding - Isokuortti, Harri; Iverson, Grant L.; Posti, Jussi P.; Ruuskanen, Jori O.; Brander, Antti; Kataja, Anneli; Nikula, Milaja; Öhman, Juha; Luoto, Teemu M. (Frontiers in Neurology, 2021)
Background: Serotonergic antidepressants may predispose to bleeding but the effect on traumatic intracranial bleeding is unknown. Methods: The rate of intracranial bleeding in patients with antidepressant medication was compared to patients not antidepressants in a cohort of patients with acute head injury. This association was examined by using a consecutive cohort of head trauma patients from a Finnish tertiary center emergency department (Tampere University Hospital, Tampere, Finland). All consecutive (2010–2012) adult patients (n = 2,890; median age = 58; male = 56%, CT-positive = 22%, antithrombotic medication users = 25%, antidepressant users = 10%) who underwent head CT due to head trauma in the emergency department were included. Results: Male gender, GCS <15, older age, and anticoagulation were associated with an increased risk for traumatic intracranial bleeding. There were 17.8% of patients not taking antidepressants and 18.3% of patients on an antidepressant who had traumatic intracranial bleeding (p = 0.830). Among patients who were taking antithrombotic medication, 16.6% of the patients not taking antidepressant medication, and 22.5% of the patients taking antidepressant medication, had bleeding (p = 0.239). In a regression analysis, traumatic intracranial hemorrhage was not associated with antidepressant use. Conclusions: Serotonergic antidepressant use was not associated with an increased risk of traumatic intracranial hemorrhage.